Anti-politics in Action? Measurement Dilemmas in the Study of Unconventional Political Participation. (September 2014) - Saunders, Clare
There are good reasons to test more refined measures of protest to better understand protesters' disaffection with and disconnection from politics. This article assesses whether disaffection and disconnection predict each of: protest participation (aggregated), participation in demonstrations, and differential participation in demonstrations. Failure to vote does not predict participation in demonstrations but positively predicts participation in "protest" (aggregated). Those who demonstrate more frequently are more likely to participate in electoral politics than less frequent demonstrators. Most protesters are at least moderately engaged with formal politics, despite lacking trust in political institutions. Protest is not, therefore, a straightforward expression of anti-politics.